Multiple stents are not superior to single stent insertion for pain relief in patients with chronic pancreatitis: a retrospective comparative study - Papalavrentios, Lavrentios; Musala, Carmen; Gkolfakis, Paraskevas; Devière, Jacques; Delhaye, Myriam; Arvanitakis, Marianna (Endoscopy International Open, 2019)
Background and study aims Patients with painful chronic pancreatitis (CP) and distal main pancreatic duct (MPD) stricture are considered candidates for treatment using a single plastic stent insertion. Multiple side-by-side stents have been proposed as an alternative treatment but comparative studies are lacking. The aim of this retrospective study is to assess differences in characteristics and treatment outcomes in patients with CP and MPD strictures treated with a different number of stents during the stenting period.Patients and methods Patients with painful CP and distal MPD obstruction requiring endoscopic treatment (01.2004 – 12.2012) were considered. The study population was divided in three groups: Patients treated with (A) exclusively one stent; (B) one or two stents; and (C) exclusively two stents during the stenting period. Patient characteristics and treatment outcomes were retrospectively assessed.Results Among 284 patients, 85 were selected according to inclusion criteria (Group A: 18, Group B: 35, Group C: 32). Median follow-up duration was 84 months. The median number of endoscopic procedures needed was higher for group B [3 (A) vs. 3 (C) vs. 4 (B), P = 0.001]. Regarding outcome, successful endoscopic treatment was lower in Group C (50 % vs. 88.2 % and 74.2 % for groups A and B, respectively; P = 0.02). This difference was attributed to better clinical outcome in Group A compared to Group C patients [OR(95%CI): 7.50 (1.46 – 38.70); P = 0.04]. Moreover, group C patients experienced higher levels of pain at the end of follow-up period [median Izbicki Score 0 (group A) vs. 0 (group B) vs. 6 (group C), P = 0.03].Conclusions In patients with painful CP and distal MPD obstruction, treatment with a single stent is associated with better clinical outcome compared to treatment with exclusively two stents during the stenting period.